CAR-T Cell Therapy: Advances in Kidney-Related Diseases - Longyuan Wu; Youqin Feng; Yue Huang; Jingjing Feng; Yongxian Hu; He Huang (Karger Publishers, 2024)
Background: Chimeric antigen receptor (CAR)-T cell therapy represents a significant advancement in the field of immunotherapy, providing targeted eradication of abnormal cells through the recognition between CAR and target antigens. This approach has garnered considerable attention due to its promising results in the clinical treatment of hematological malignancies and autoimmune diseases. As the focus shifts toward exploring novel targets and expanding the application of CAR-T cell therapy to solid tumors, including renal malignancies, researchers are pushing the boundaries of this innovative treatment. However, it is crucial to address the observed comorbidities associated with CAR-T cell therapy, particularly nephrotoxicity, due to the superseding release of cytokines and impairment of normal tissue. Summary: Our review discusses the research strategies and nephrotoxicity related to CAR-T cell therapy in various kidney-related diseases and provides insights into enhancing investigation and optimization. Key Messages: CAR-T cell therapy has captured the attention of researchers and clinicians in the treatment of renal malignancies, multiple myeloma, systemic lupus erythematosus, and acquired immunodeficiency syndrome, which may lead to potential nephrotoxicity as they involve primary or secondary kidney complications. Understanding and summarizing the current research progress of CAR-T cell therapies can provide valuable insights into novel targets and combinations to optimize research models and enhance their clinical value.